Impact of interpregnancy interval on long-term childhood neoplasm of the offspring. (12th December 2022) - Toledano, Roni; Wainstock, Tamar; Sheiner, Eyal; Kessous, Roy
Abstract: Background: The possible impact of interpregnancy interval (IPI) on perinatal outcomes has long been studied, however, a definition of the optimal interval is still not clear. Both short and long IPIs have been associated with obstetrical syndromes and short and long-term complications. In this study, we sought to explore the impact of IPI on the hazard for neoplasm of the offspring, thus contribute to the present literature in determining the preferred birth spacing. Objective: We aim to investigate the association between short and long IPIs and the hazard for childhood neoplasm of the offspring. Methods: A population-based retrospective cohort analysis comparing offspring neoplasm hazard following three different IPIs. Exposure was defined as short (<6 months), or long (>60 months) IPIs, whereas intermediate IPI (6 months − 60 months) served as the comparison group. The study included singleton live births in a tertiary regional hospital between 1991 and 2014. Offspring were followed for 18 years, and all hospitalization records for neoplasm diagnoses were collected. Kaplan–Meier survival curves were used for the cumulative incidence of neoplasm morbidity, and Cox proportional hazards models were used to control for confounders. Results: During the study period, 144, 397 deliveries met the inclusion criteria. Of those, 18, 947 (13.1%) occurred in women with short IPI, 114, 012 (79%) in women with intermediate IPI, and 11, 438 (7.9%) in women with long IPI. 61 benign neoplasms and 80 malignant neoplasms were registered in offspring born after long IPI. The total percentage of neoplasm were the highest in the long IPI group versus the intermediate and short IPI groups (malignant − 0.7%, 0.6%, 0.5% respectively, benign − 0.5%, 0.4%, 0.3% respectively). Controlling for maternal age, diabetes mellitus, preterm delivery, birth weight, smoking, cesarean section, and fertility treatments, long IPI was found to be independently associated with high hazard for long-term pediatric neoplasm related hospitalizations (adjusted HR 1.39, 95% CI 1.09, 1.77). Short IPI may be associated to decreased hazard for childhood neoplasms (adjusted HR 0.74, 95% Cl 0.59, 0.92). Conclusions: Long IPI is associated with a high hazard for childhood neoplasms, compared with intermediate and short IPIs. Short IPI may be associated with decreased hazard for childhood neoplasms.